X-ray diffraction and secondary ion mass spectrometry investigations of GaN films grown on (0 0 1) and (1 1 0) MgF2 substrates by plasma-assisted molecular beam epitaxy (PA-MBE). (15th November 2020) - Meyer, Kevin; Buchholz, Martin; Uxa, Daniel; Dörrer, Lars; Schmidt, Harald; Schaadt, Daniel M.
Abstract: Gallium nitride (GaN) growth on two different crystallographic orientations of magnesium fluoride (MgF2 ) by plasma-assisted molecular beam epitaxy (PA-MBE) was investigated by x-ray diffraction (XRD) and secondary ion mass spectrometry (SIMS) under different growth temperatures. (0 0 1) and (1 1 0) MgF2 substrates were used. Four different growth temperatures, 525 ∘ C, 600 ∘ C, 650 ∘ C and 700 ∘ C, were tested for both substrate orientations. The formation of hexagonal α-GaN and cubic β-GaN is mainly influenced by the growth temperature and the substrate orientation. At lower temperatures a mixture of both crystalline structures were formed independent of the MgF2 orientation. One of the two GaN structures disappeared with an increasing growth temperature dependent on the substrate orientation. A layer of mainly cubic β-GaN with inclusions of hexagonal one is formed at a growth temperature of 700 ∘ C on (0 0 1) MgF2, whereas the layer on (1 1 0) MgF2 consists only of hexagonal α-GaN at a growth temperature of 700 ∘ C. SIMS measurement showed that magnesium and fluorine can be found in the whole GaN layer at 650 ∘ C. At lower temperature only gallium and nitrogen are in the first part of the layer. The magnesium and fluorine diffusion into GaN could be one reason for the change of the GaN crystal structure and are an indication for a significant interaction between layer and substrate at higher growth temperatures.